Can the mechanical activation (polishing) of screen-printed electrodes enhance their electroanalytical response?. Issue 9 (17th February 2016) - Cumba, Loanda R.; Foster, Christopher W.; Brownson, Dale A. C.; Smith, Jamie P.; Iniesta, Jesus; Thakur, Bhawana; do Carmo, Devaney R.; Banks, Craig E.
Abstract : The use of mechanical activation (polishing) as a pre-treatment for screen-printed electrodes (SPEs) is reported and shown to give rise to an improved electroanalytical response. Abstract : The mechanical activation (polishing) of screen-printed electrodes (SPEs) is explored and shown to exhibit an improved voltammetric response (in specific cases) when polished with either commonly available alumina slurry or diamond spray. Proof-of-concept is demonstrated for the electrochemical sensing of nitrite where an increase in the voltammetric current is found using both polishing protocols, exhibiting an improved limit of detection (3 σ ) and a two-fold increase in the electroanalytical sensitivity compared to the respective un-polished counterpart. It is found that mechanical activation/polishing increases the C/O ratio which significantly affects inner-sphere electrochemical probes only (whereas outer-sphere systems remain unaffected). Mechanical activation/polishing has the potential to be a simple pre-treatment technique that can be extended and routinely applied towards other analytes for an observable improvement in the electroanalytical response.